Gender Effects of Social Security Reform in Chile - Cox Edwards, Alejandra (Washington, DC: World Bank, 2014)
In 1981 Chile replaced a mature government-run social security system that operated on a pay-as-you-go basis with a privately managed system based on individual retirement accounts. The new system is more fiscally sustainable because pension benefits are defined by contributions. The minimum pension guaranteed to beneficiaries with at least 20 years is funded from general taxes, preserving the tight matching between contributions and benefits. The new system also eliminates several cross-subsidies. Men and women with less than secondary education gain under the new system, but single women with more education lose. Comparison of the old and the new systems reveals a complex set of factors that cause gender effects given constant behavior or change behavior across genders.